(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Nonclassical congenital adrenal hyperplasia (NCCAH) remains systematically underdiagnosed in women of fertile age due to phenotypic overlap with polycystic ovary syndrome. This study presents development and genetic validation of the NCCAHSCREENF clinical screening scale, integrating hormonal, dermatological, reproductive, and molecular criteria to enhance early diagnostic precision in routine endocrinological and gynecological practice.